Działalność kobiet w Związku Polaków "Zgoda" w RFN - Kamiński, Artur (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
The article aims at presenting the activity of women – members of the Union of Poles “Unity” in West Germany. In particular, the issues raised at conferences and conventions and the journalistic activity of the female members of the Union were outlined. The article is an attempt to answer the question on the role of women from the Union in popularization of the statutory ideas of this organization
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne